EXPRESSING CONDOLENCES TO OBITUARIES IN A WHATSAPP GROUP OF INDONESIAN LECTURERS - Yuliani Kusuma Putri; Asep Achmad Muhlisian (Jurnal Sosioteknologi, 2019)
This study is aimed to investigate condolence strategies used by a group of Indonesians lecturers to obituaries announced in a WhatsApp group. The study seeks to answer kind of condolence strategies used by the members and the condolence sequences expressed by the members. Since data is gathered from a computer mediated communication, i.e. instant messaging, this study uses a netnopragmatic approach, an approach to studying the use of language in online communities, coined from netnography research method, an ethnographic research done in online communities. The study shows that the members mostly recite Quranic verses and pray for God's mercy and forgiveness for the deceased in expressing their condolences. The result is due to the faith that most members have, i.e. Islam, which teaches them to pray when they first hear bad news. It can be clearly seen that expressing condolences is influenced by the faith of the condolence giver; not the religion that the deceased held.